Efficacy of the Addition of Robot-assisted Radical Cystectomy with Extracorporeal Urinary Diversion after an Enhanced Recovery Protocol - Nagayama, Jun; Yamamoto, Akiyuki; Naito, Yushi; Kamikawa, Hiroki; Kanazawa, Hideyuki; Asano, Akiyuki; Sho, Norie; Terashima, Yasuhiro (Urology Journal, 2024)
Purpose: It is unclear if robotic radical cystectomy with extracorporeal urinary diversion (eRARC) provides additional benefit when performed along with enhanced recovery after surgery (ERAS). We assessed the additional efficacy of eRARC in terms of perioperative outcomes. Materials and Methods: We retrospectively assessed 143 patients undergoing radical cystectomy with urinary diversion between June 2010 and December 2021 at a single center. The patients were assigned to three groups: open radical cystectomy (ORC) with conventional recovery after surgery (CRAS) [Group A], ORC with ERAS [Group B], and eRARC with ERAS [Group C]. A propensity score-matched analysis was performed to evaluate how ERAS and eRARC affected outcomes respectively. Meanwhile, multivariable analysis was used to detect the predictors of prolonged length of hospital stay (LOS). Results: The median LOS was shorter after ERAS and eRARC. In the propensity score-matched analysis, ERAS was linked to a significantly shorter median LOS (28.0 vs. 20.0 days, P < .001), but eRARC was not associated with a shorter LOS (19.0 vs. 17.5 days, P = .21). Neither ERAS nor eRARC were connected with a reduce in complication rate. Following multivariable analysis, ERAS was found to be independently associated with shorter LOS (OR=0.23, P < .001), but eRARC demonstrated no such correlation (OR=0.29, P = .096). Conclusion: ERAS had strong association with shorter LOS, although eRARC did not contribute to additional efficacy. Neither ERAS nor eRARC decreased the complication rate.